IVIg increases interleukin‐11 levels, which in turn contribute to increased platelets, VWF and FVIII in mice and humans. (22nd February 2021) - Nguyen, A.; Repesse, Y.; Ebbo, M.; Allenbach, Y.; Benveniste, O.; Vallat, J. M.; Magy, L.; Deshayes, S.; Maigné, G.; de Boysson, H.; Karnam, A.; Delignat, S.; et al.
Summary: The mechanisms of action of intravenous immunoglobulins (IVIg) in autoimmune diseases are not fully understood. The fixed duration of efficacy and noncumulative effects of IVIg in immune thrombocytopenia (ITP) and acquired von Willebrand disease (AVWD) suggest other mechanisms besides immunological ones. Additionally to the peripheral destruction of platelets in ITP, their medullary hypoproduction emerged as a new paradigm with rescue of thrombopoietin receptor agonists (TPO‐RA). In an ITP mouse model, interleukin (IL)‐11 blood levels increase following IVIg. IL‐11 stimulates the production of platelets and other haemostasis factors; recombinant IL‐11 (rIL‐11) is thus used as a growth factor in post‐chemotherapy thrombocytopenia. We therefore hypothesized that IVIg induces IL‐11 over‐production, which increases platelets, VWF and factor VIII (FVIII) levels in humans and mice. First, in an ITP mouse model, we show that IVIg or rIL‐11 induces a rapid increase (72 h) in platelets, FVIII and VWF levels, whereas anti‐IL‐11 antibody greatly decreased this effect. Secondly, we quantify for the first time in patients with ITP, AVWD, inflammatory myopathies or Guillain–Barré syndrome the dramatic IL‐11 increase following IVIg, regardless of the disease. As observed in mice, platelets, VWF and FVIII levels increased following IVIg. The late evolution (4 weeks) of post‐IVIg IL‐11 levels overlapped with those of VWF and platelets. These data may explain thrombotic events following IVIg and open perspectives to monitor post‐IVIg IL‐11/thrombopoietin ratios, and to assess rIL‐11 use with or without TPO‐RA as megakaryopoiesis co‐stimulating factors to overcome the relative hypoproduction of platelets or VWF in corresponding autoimmune diseases, besides immunosuppressant. Abstract : This study shed new light on IL‐11 as a mechanistic missing link between IVIg and the timing of the stereotypic increases/decreases in VWF, FVIII and platelet levels. Therefore, rIL‐11 may represent a promising alternative to IVIg to overcome the insufficient compensatory production of platelets or VWF in corresponding autoimmune diseases, especially in the context of worldwide shortage of IVIg products. These data may explain thrombotic events following IVIg and raise caution in autoimmune diseases treated with IVIg associated or not with antiphospholipid syndrome or ITP.